Jennie Cox Johnson (wife of C. H. Johnson) and Rodney Johnson (son of C. H. Johnson) (1915)
The Johnsons at home near Stenner Creek, 1915. Rodney V. Johnson Sr. and his mother, Jennie W. Johnson. View toward the east. Note Cal Poly buildings, right center. See Stechman, "An Illustrated History of Land Acquisition and Development for Agricultural Education"